Assessing the Impact of Improvements in PASI and Itch Scores on Patients' Quality of Life in the Treatment of Psoriasis - Gil Yosipovitch; Yan Dong; Russel Burge; Baojin Zhu; David Shrom; Alexa B. Kimball (Medical Journals Sweden, 2019)
Abstract is missing (Short communication)